PENGARUH PEER TEACHING MODEL TERHADAP KETERAMPILAN GERAK DASAR PUKULAN BULUTANGKIS PADA SISWA KELAS VIII SMP BINTANG TIMUR - Styven Mulia Silitonga; Akhmad Dimyati; Evi Susanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of making this thesis is to understand the impact of peer teaching methods in learning badminton on basic badminton hitting skills among grade VIII students of SMP Bintang Timur. To answer the research problems that have been stated, the author applies a quantitative approach by means of experiments. This research was carried out at SMP Bintang Timur by choosing one class as a sample, namely class VIII-B with a total of 26 students out of 187 students in five classes in class VIII. This research was carried out in three stages, namely pretest, treatment, and posttest. The pretest aims to find out the initial ability of hitting skills in badminton learning before getting treatment. After the pretest, the researcher conducted treatment in the form of eight peer teaching sessions. After the treatment was completed, the researcher conducted a posttest to check whether there was an impact of the peer teaching model in learning badminton on basic badminton hitting skills in grade VIII students of SMP Bintang Timur. The results of this study show that there is an impact of the peer teaching model in learning badminton on badminton hitting skills in grade VIII students of SMP Bintang Timur with the following explanation: based on the value of sig (2-tailed) it is obtained that the value of sig (2-tailed) is 0.000 < 0.05 so that H0 is rejected and Ha is accepted, which shows that there is an influence of the peer teaching model on basic hitting movement skills in learning badminton in grade VIII students of SMP Bintang Timur. Therefore, it is hoped that through peer teaching it can help improve hitting skills in badminton learning.